DIREITO E POLÍTICAS PÚBLICAS: A REGULAÇÃO DOS AMBIENTES ALIMENTARES NO BRASIL - R. Coutinho, Diogo; A. Cabrera, Oscar; Barbosa, Isabel; Levy, Mariana; Carolina Foss, Maria; Rebêlo Ferreira, Alexandre; Kira, Beatriz; Saito, Carolina; Kharmandayan, Luiza; Piva Adami, Mateus; et al. (REI - REVISTA ESTUDOS INSTITUCIONAIS, 2022)
Apresentação do número especial realizado em parceria envolvendo o Grupo Direito e Políticas Públicas da Faculdade de Direito da Universidade de São Paulo, o Global Center for Legal Innovation on Food Environments do O’Neill Institute for National and Global Health Law (Georgetown University Law Center) e a Revista Estudos Institucionais (REI). A partnership between Grupo Direito e Políticas Públicas and the O’Neill Institute for National and Global Health Law (Global Center for Legal Innovation on Food Environments). The project “Law, Policy and Public Health: the regulation of food environments in Brazil”, a partnership between Grupo Direito e Políticas Públicas and the Global Center for Legal Innovation on Food Environments (O’Neill Institute for National and Global Health Law at Georgetown Law), aims to generate knowledge and raise awareness of the legal arrangements and strategies which impact on food environments in Brazil. The research developed under this project investigates rules, institutions and actors that shape food environments, and to what extent they act as enablers or obstacles to the protection of the rights of individual users and collectives, and to the promotion of their economic and social rights and interests in a sustainable and healthy way. In addition, it aims to create a new community of researchers and policymakers, centered on the ambition to inform policy and regulatory actions and responses.